The history of wheat breeding in Algeria - Abdelkader B. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Research on wheat in Algeria started several centuries ago. In the pre-colonization period (before 1830) it was just a botanical curiosity and from then acquired the status of real plant breeding using most of the modes to increase genetic variability in new varieties (i.e. hybridization, selection, testing, release), to develop better varieties for a rapidly increasing population. For a long time researchers thought that bread wheat did not exist in North Africa before the arrival of the Arabs. In 1930, during the French occupation of Algeria, only durum wheat was cultivated in the plain areas. Bread wheat was considered a separate crop and was only found as undesired mixtures in durum fields. From the end of the XVIIIth and early XIXth century, only durum wheat was given importance by the farmers and was largely cultivated. There are archeological, historical and phylogenetic arguments that support the presence of durum wheat in Algeria. After the colonists and first botanical studies era to the post independency period, several germplasm enhancement programs were launched aimed at good adaptation and high yield potential. Collaboration with International Centers, from the late 1960’s (FAO, European CC and CIMMYT) was very strong and interactive and achieved all planned objectives. In 1980 ICARDA participated in contributing to Algeria’s field crops research and development. In light of achieving the main government goal to ensure food security by 2015 by producing 10 million tons of wheat a new bilateral (INRAA/ITGC) research approach (NWIP) was launched with the collaboration of ICARDA. Regional and multidisciplinary approaches have been adopted and several promising cultivars were developed through a participatory approach as a final step. This material helped in evolution of good yields during this last decade.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)